Očetje in sinovi v maturitetnih romanih Konje krast in Figa - Zupan Sosič, Alojzija (Jezik in slovstvo, 2020)
The graduation novels Konje krast (Out Stealing Horses) and Figa (Fig) address less common, almost taboo topics in the father-son relationship, such us overcoming child trauma and silence on the loss of a loved one. The study focuses on the following story junctions: the father's absence, pain as a place of overcoming and exceeding the past, the intertwining of time, the placement of the family story in the social context, and the significance of nature for the main literary characters. Numerous quality similarities at the story level are, at the end, joined by a discussion of the narrative qualities of both novels, which brings a significant difference: Konje krast contains higher narrative quality whereas Figa is a novel of lower quality. In Figa, partial trivialisation at the narrative level involves the (trivial) procedures of simplification, redundancy, monosemicity and a lack of self-referentiality. The consequences of these procedures are unreduced narrativity, linear reporting, and a lack of symbolism and metaphor or aesthetic concentration.
Keywords: fathers and sons; graduation novel; literarne študije; literary studies; maturitetni roman; norveška književnost; Norwegian literature; očetje in sinovi; Petterson, Per; primerjalne analize; Slovenian literature; slovenska književnost; story junctions; Vojnović, Goran; zgodbena stičišča